Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment
Through step-by-step blending and carbon cladding design, the problems of insufficient mixing uniformity and poor electrochemical performance of lithium iron phosphate positive electrode materials in the prior art are solved, and high compaction density and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411752470.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-30
AI Technical Summary
The prior art is difficult to prepare high-performance lithium iron phosphate positive electrode material by dry mixing stage preparation, and the mixing uniformity is insufficient, resulting in the failure to obtain high compaction density and excellent electrochemical properties.
The positive electrode active material was prepared by step-by-step blending. Two characteristic peaks were presented through the particle size distribution curve of the primary particles, the main peak and peak positions were 100nm-250nm, and the second characteristic peak and peak positions were 270nm-400nm. Combined with the design of the carbon cladding layer, high uniformity and high compaction density were achieved.
It realizes a high uniform carbon cladding layer of the cathode active material, which has high compaction density and excellent electrochemical properties, and is suitable for large-scale industrial production.
Smart Images

Figure CN119560558A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium iron phosphate materials have become the most widely used positive electrode materials in lithium-ion batteries due to their stable structure, good safety and long cycle life. However, with the development of society and technology, people have put forward higher requirements for energy storage devices including lithium-ion batteries. Therefore, improving the energy density of lithium iron phosphate batteries has become a hot research topic in the field in recent years. Grading of large and small particles is an effective method to increase the compaction density of powders. It is currently known that lithium iron phosphate materials with different particle sizes are dry mixed and graded to prepare high-density lithium iron phosphate positive electrode materials. However, the above scheme adds the preparation of lithium iron phosphate precursors with different particle sizes, and the materials need to be dry mixed. The mixing uniformity cannot be guaranteed. In fact, high-performance lithium iron phosphate positive electrode materials cannot be obtained. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. The positive electrode active material can achieve a graded structure, has a highly uniform carbon coating layer, has high compaction and better electrochemical performance, and the preparation method of the positive electrode active material is simple and suitable for large-scale industrial production applications.
[0004] To this end, the present invention provides a first aspect of a step-by-step blended positive electrode active material, including lithium iron phosphate, wherein the lithium iron phosphate is a secondary particle formed by agglomeration of primary particles, and the particle size number distribution curve of the primary particles presents two characteristic peaks;
[0005] Among them, the highest characteristic peak is the first characteristic peak, and the first characteristic peak is at R A 100nm-250nm, the first characteristic peak is R A The corresponding quantity percentage X A 44%-54%;
[0006] The second characteristic peak of the primary particles has a peak position R B The second characteristic peak is 270nm-400nm, and the peak position of the second characteristic peak is R B The corresponding quantity percentage X B It is 2.0%-8.0%.
[0007] The positive electrode active material provided by the present invention is multi-stage blended, and the particle size distribution curve of the primary particles presents two characteristic peaks, corresponding to the presence of particles of various particle size distributions in the positive electrode active material, which work together to form a step-by-step blend. The main peak of the two characteristic peaks is between 100nm and 250nm, corresponding to the number percentage X A It is 44%-54%, indicating that the positive electrode active material contains a sufficient number of nanoscale single crystal particles, which can well fill the gaps in large particles to obtain ultra-high compaction density. At the same time, the nanoscale single crystals can improve the problem of long ion migration path, so that the secondary battery containing the positive electrode active material can obtain higher capacity and higher rate performance.
[0008] According to an embodiment of the present invention, in the particle size distribution curve of the primary particles, there is a first minimum value R between the first characteristic peak and the second characteristic peak. AO , the first minimum value R AO The corresponding particle size range is 250nm-300nm, and the first minimum value R AO The corresponding quantity percentage X AO It is 1.0%-5.0%.
[0009] According to an embodiment of the present invention, the peak index λ of the positive electrode active material is 5%-20%;
[0010] Where λ=(X B -X AO ) / X B ×100%;
[0011] X AO is the first minimum value R between the first characteristic peak and the second characteristic peak AO The corresponding quantity percentage;
[0012] X B The second characteristic peak position R B The corresponding percentage of quantity.
[0013] According to an embodiment of the present invention, the D 50 0.1μm-1.0μm.
[0014] According to an embodiment of the present invention, the D 50 0.5μm-1.6μm.
[0015] According to an embodiment of the present invention, the compaction density of the positive electrode active material is 2.55 g / cm 3 -2.75g / cm 3 .
[0016] According to an embodiment of the present invention, the specific surface area of the positive electrode active material is 11m 2 / g-15m 2 / g.
[0017] According to an embodiment of the present invention, the positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate;
[0018] Wherein, the matrix has a composition shown in Formula I:
[0019] Li 1+a Fe b M c (PO4) d Formula I;
[0020] Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1;
[0021] M is selected from at least one of La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al.
[0022] According to an embodiment of the present invention, M is Sb, and at least one of Al, W, Co, V and Ti.
[0023] According to an embodiment of the present invention, based on the total weight of the positive electrode active material, the content of the carbon coating layer is 0.5 wt %-2 wt %, preferably 1 wt %-1.5 wt %.
[0024] The second aspect of the present invention provides a method for preparing the positive electrode active material according to the first aspect, the preparation method comprising:
[0025] A first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source is prepared, and the first slurry is obtained by grinding;
[0026] A second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source is prepared, and the second mixed solution is ground to obtain a second slurry;
[0027] The first slurry and the second slurry are mixed, and the mixture is spray-dried and sintered to obtain the positive electrode active material;
[0028] Wherein, the particle size of the first iron phosphate is 80nm-200nm; the particle size of the second iron phosphate is 60nm-150nm;
[0029] The particle size D of the first slurry 50 Smaller than the particle size D of the second slurry 50 , and the difference is not less than 0.15μm.
[0030] The present invention prepares a first slurry with a smaller particle size and a second slurry with a larger particle size, and slurries of different particle sizes are blended. Since the slurry particles are in a solution state, the mixing uniformity is excellent, and the mixed gradation of large and small particles is achieved in the slurry stage. In the subsequent sintering and crystallization process, the particle growth degree grows with the level of the primary particles, which greatly optimizes the particle gradation of the material, and the particles are more tightly bound, so that a positive electrode active material with both high capacity and high compaction density performance is prepared. At the same time, the preparation method has a simple process flow and low equipment requirements, and is suitable for application in large-scale industrial production.
[0031] According to an embodiment of the present invention, the specific surface area of the first iron phosphate is 7 m 2 / g-13m 2 / g.
[0032] According to an embodiment of the present invention, the specific surface area of the second iron phosphate is 5m 2 / g-12m 2 / g.
[0033] According to an embodiment of the present invention, the first iron phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.960-0.980.
[0034] According to an embodiment of the present invention, the second ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.950-0.970.
[0035] According to an embodiment of the present invention, the first lithium source and the second lithium source are independently selected from one of lithium hydroxide, lithium carbonate and lithium acetate.
[0036] According to an embodiment of the present invention, the lithium iron molar ratio Li / Fe of the first lithium source and the first iron phosphate is 1.01-1.07.
[0037] According to an embodiment of the present invention, the lithium iron molar ratio Li / Fe of the second lithium source and the second iron phosphate is 1.01-1.07.
[0038] According to an embodiment of the present invention, the first carbon source is selected from at least one of glucose, sucrose, starch, polyethylene glycol, and citric acid.
[0039] According to an embodiment of the present invention, the amount of the first carbon source added satisfies that the mass ratio of carbon to the mass ratio of the positive electrode active material is 1.0 wt%-1.8 wt%.
[0040] According to an embodiment of the present invention, the second carbon source is selected from at least one of glucose, sucrose, polyethylene glycol, and citric acid.
[0041] According to an embodiment of the present invention, the amount of the second carbon source added satisfies that the mass ratio of carbon to the mass ratio of the positive electrode active material is 1.0wt%-1.4wt%.
[0042] According to an embodiment of the present invention, the solid content of the first slurry is 35wt%-50wt%.
[0043] According to an embodiment of the present invention, the solid content of the second slurry is 35wt%-50wt%.
[0044] According to an embodiment of the present invention, D 50 0.15μm-0.50μm.
[0045] According to an embodiment of the present invention, D 50 0.35μm-1.00μm.
[0046] According to an embodiment of the present invention, the air inlet temperature of the spray drying is 220°C-280°C, and the air outlet temperature is 100°C-120°C.
[0047] According to an embodiment of the present invention, the first slurry and the second slurry are mixed in a mass ratio of (3:7)-(7:3).
[0048] According to an embodiment of the present invention, the sintering temperature is 720° C.-830° C., and the sintering time is 6 h-12 h.
[0049] The third aspect of the present invention provides a positive electrode plate, the positive electrode plate comprising the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect. Thus, the plate has a high compaction density and exhibits high capacity and high rate performance in electrochemical work.
[0050] The fourth aspect of the present invention provides a battery, the battery comprising the positive electrode sheet of the third aspect, so that the battery has good electrochemical performance.
[0051] A fifth aspect of the present invention provides an electrical device, wherein the electrical device comprises the battery described in the fourth aspect.
[0052] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0054] Figure 1 The SEM image of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0055] Figure 2The XRD pattern of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0056] Figure 3 The particle size distribution curve of the primary particles of the lithium iron phosphate positive electrode active material prepared in Example 1 of the present invention is shown;
[0057] Figure 4 The particle size distribution curve of the primary particles of the lithium iron phosphate positive electrode active material prepared in Comparative Example 1 of the present invention is shown;
[0058] Figure 5 The charge and discharge curve of the button half-cell prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0059] The following embodiments of the technical solution of the present invention are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0060] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0061] "Scope" disclosed in the present invention is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0062] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0063] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0064] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0065] A first aspect of the present invention provides a positive electrode active material, wherein the positive electrode active material is a secondary particle formed by agglomeration of primary particles, and a particle size number distribution curve of the primary particles presents two characteristic peaks;
[0066] Among them, the highest characteristic peak is the first characteristic peak, and the first characteristic peak is at R A 100nm-250nm, the first characteristic peak is R A The corresponding quantity percentage X A 44%-54%;
[0067] The second characteristic peak of the primary particles has a peak position R B The second characteristic peak is 270nm-400nm, and the peak position of the second characteristic peak is R B The corresponding quantity percentage X B It is 2.0%-8.0%.
[0068] The particle size distribution curve of the primary particles of the positive electrode active material provided by the present invention presents two characteristic peaks, indicating that the positive electrode active material contains primary particles of at least two particle sizes. The main peak of the two characteristic peaks is located at 100nm-250nm, corresponding to the number percentage X AIt is 44%-54%, indicating that the positive electrode active material contains a sufficient number of nano-scale single crystal particles, which can be filled in the gaps of large particles to significantly improve the overall powder compaction density. At the same time, the grading of particles of different particle sizes can increase the solid volume fraction and bulk density in the battery, increase the active material loading per unit volume of the slurry layer, that is, increase the filling density, thereby achieving the purpose of increasing the battery capacity and energy density. The gaps and pores of the active particles are diffusion channels for lithium ions. The grading of large and small particles allows the active particles to have more surface contact with the electrolyte, increasing the utilization rate of the active material, facilitating the charge transfer at the electrode / electrolyte interface, and improving the specific capacity of the battery.
[0069] The particle size distribution curve is obtained by plotting the particle size of the primary particles as the abscissa and the percentage of the sum of the number of particles having the particle size in the total number of all particles as the ordinate.
[0070] According to a specific embodiment of the present invention, the second characteristic peak of the primary particles is at a peak position R B The second characteristic peak is 270nm-400nm, and the peak position of the second characteristic peak is R B The corresponding quantity percentage X B The second characteristic peak is 270nm-400nm, which can take into account the capacity and cycle balance of the particles themselves. At the same time, the second characteristic peak peak position R B The corresponding quantity percentage X B It is 2.0%-8.0%, which further ensures the high compaction density, cycle balance and rate performance of the material.
[0071] According to a specific embodiment of the present invention, there is a first minimum value R between the first characteristic peak and the second characteristic peak. AO , the first minimum value R AO The corresponding particle size range is 250nm-300nm, and the first minimum value R AO The corresponding quantity percentage X AO The ratio of the first characteristic peak to the second characteristic peak is 1.0% to 5.0%.
[0072] According to a specific embodiment of the present invention, the peak index λ of the positive electrode active material is 5%-20%;
[0073] Where λ=(X B -X AO ) / X B ×100%;
[0074] X AO is the first minimum value R between the first characteristic peak and the second characteristic peak AO The corresponding quantity percentage;
[0075] X B The second characteristic peak position R B The corresponding percentage of quantity.
[0076] When the particle size distribution of the second characteristic peak is too wide, and small particles are mixed at this time, then the peak index λ of the positive electrode active material is small. At this time, the depth of lithium insertion and extraction of the material during the charge and discharge process is obviously different, resulting in a large capacity difference. The intrinsic charge transfer impedance leads to excessive impedance and rate differences, which reduces the overall capacity and rate performance of the material. Therefore, when the peak index λ meets the definition of the present invention, on the one hand, large and small particles can be effectively distributed in the structure to form a filling effect, so that the positive electrode active material obtains a higher compaction density; on the other hand, the mixing of excessively large particles is avoided, so that the large particles can maintain good capacity and cycle performance.
[0077] According to a specific embodiment of the present invention, the D 50 As some specific examples, the D 50 It is 0.1μm, 0.5μm, 1.0μm, etc.
[0078] According to a specific embodiment of the present invention, the D 50 As some specific examples, the secondary particles have a D 50 0.5μm, 1μm, 1.5μm, 1.6μm, etc.
[0079] According to a specific embodiment of the present invention, the compaction density of the positive electrode active material is 2.55 g / cm 3 -2.75g / cm 3 As some specific examples, the compaction density of the positive electrode active material is 2.55 g / cm 3 , 2.65g / cm 3 , 2.75g / cm 3 wait.
[0080] According to a specific embodiment of the present invention, the specific surface area of the positive electrode active material is 11m 2 / g-15m 2 As some specific examples, the specific surface area of the positive electrode active material is 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m2 / g, 15m 2 / g, etc.
[0081] According to a specific embodiment of the present invention, the positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate;
[0082] Wherein, the matrix has a composition shown in Formula I:
[0083] Li 1+a Fe b M c (PO4) d Formula I;
[0084] Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1;
[0085] M is at least one selected from La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al;
[0086] Preferably, M is Sb and at least one of Al, W, Co, V and Ti. That is, M must contain Sb and at least one of Al, W, Co, V and Ti.
[0087] According to a specific embodiment of the present invention, based on the total weight of the positive electrode active material, the content of the carbon coating layer is 0.5wt%-2wt%. As some specific examples, the content of the carbon coating layer is 0.5wt%, 1wt%, 1.5wt%, 2wt%, etc., preferably 1wt%-1.5wt%.
[0088] A second aspect of the present invention provides a method for preparing the above-mentioned positive electrode active material, the preparation method comprising:
[0089] (1) A first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source is prepared, and a first slurry is obtained by grinding.
[0090] According to a specific embodiment of the present invention, the particle size of the first iron phosphate is 80nm-200nm. As some specific examples, the particle size of the first iron phosphate may be 80nm, 100nm, 150nm, 200nm, etc.
[0091] According to a specific embodiment of the present invention, the specific surface area of the first iron phosphate is 7m 2 / g-13m 2 / g, as some specific examples, the specific surface area of the first iron phosphate may be 7m 2 / g, 8m 2 / g, 9m2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, etc. Further, the first ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.960-0.980, such as 0.960, 0.970, 0.980, etc.
[0092] According to a specific embodiment of the present invention, the specific type of the first lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the first lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium acetate, preferably lithium carbonate, and more preferably lithium carbonate with a purity of ≥99.5%.
[0093] According to a specific embodiment of the present invention, the lithium iron molar ratio Li / Fe of the first lithium source and the first iron phosphate is 1.01-1.07, for example, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, etc.
[0094] According to a specific embodiment of the present invention, the specific type of the first carbon source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the first carbon source can include at least one of glucose, sucrose, starch, polyethylene glycol, and citric acid. Further, the amount of the first carbon source added satisfies that the carbon mass accounts for 1.0wt%-1.8wt% of the mass ratio of the positive electrode active material, such as 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, etc.
[0095] According to a specific embodiment of the present invention, the specific type of the first M source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the first M source may include at least one of the salts, hydroxides, and oxides that can provide at least one element among La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al, preferably titanium dioxide, ammonium metavanadate, tungsten trioxide, magnesium oxide, cobalt oxyhydroxide, niobium pentoxide, antimony trioxide, and aluminum trioxide, wherein the addition amounts of titanium dioxide, ammonium metavanadate, tungsten trioxide, and antimony trioxide meet the titanium, vanadium, tungsten, and antimony contents of the target positive electrode active material of 1000ppm-5000ppm, 1000ppm-2000ppm, 500ppm-2000ppm, and 500-2000ppm, respectively.
[0096] According to a specific embodiment of the present invention, the preparation method of the first mixed solution is not particularly limited, and it does not affect subsequent grinding, spray drying and other steps. Specifically, the first mixed solution can be obtained by dissolving the first iron phosphate, the first lithium source, the first carbon source, and the first M source in a solvent, and the solvent includes but is not limited to deionized water.
[0097] According to a specific embodiment of the present invention, the solid content of the first slurry is 35wt%-50wt%, and the grinding is performed so that the particle size D of the first slurry is 50 The grinding method is not particularly limited and can be selected according to the actual situation in the art, as long as the particle size of the slurry is within the target range, such as by sand grinding.
[0098] (2) preparing a second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source, and grinding the mixture to obtain a second slurry.
[0099] According to a specific embodiment of the present invention, the particle size of the second iron phosphate is 60nm-150nm. As some specific examples, the particle size of the second iron phosphate may be 60nm, 80nm, 100nm, 120nm, 140nm, 150nm, etc.
[0100] According to a specific embodiment of the present invention, the specific surface area of the second iron phosphate is 5m 2 / g-12m 2 / g, as some specific examples, the specific surface area of the second iron phosphate may be 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, etc. Further, the second ferric phosphate satisfies an iron-phosphorus molar ratio Fe / P of 0.950-0.970, such as 0.950, 0.960, 0.970, etc.
[0101] According to a specific embodiment of the present invention, the specific type of the second lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the second lithium source may include at least one of lithium hydroxide, lithium carbonate, and lithium acetate, preferably lithium carbonate, and more preferably lithium carbonate with a purity of ≥99.5%.
[0102] According to a specific embodiment of the present invention, the lithium iron molar ratio Li / Fe of the second lithium source and the second iron phosphate is 1.01-1.07, for example, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, etc.
[0103] According to a specific embodiment of the present invention, the specific type of the second carbon source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the second carbon source can include at least one of glucose, sucrose, polyethylene glycol, and citric acid. Further, the amount of the second carbon source added satisfies that the carbon mass accounts for 1.0wt%-1.4wt% of the mass ratio of the positive electrode active material, such as 1.0wt%, 1.2wt%, 1.4wt%, etc.
[0104] According to a specific embodiment of the present invention, the specific type of the second M source is not particularly limited, and those skilled in the art can select it according to actual conditions. For example, the second M source may include at least one of the salts, hydroxides, and oxides that can provide at least one element among La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al, preferably aluminum oxide, titanium dioxide, ammonium metavanadate, tungsten trioxide, magnesium oxide, cobalt oxyhydroxide, niobium pentoxide, and antimony trioxide, wherein the addition amounts of titanium dioxide, ammonium metavanadate, tungsten trioxide, and antimony trioxide meet the titanium, vanadium, tungsten, and antimony contents of the target positive electrode active material of 1000ppm-5000ppm, 1000ppm-2000ppm, 500ppm-2000ppm, and 500ppm-2000ppm, respectively.
[0105] According to a specific embodiment of the present invention, the preparation method of the second mixed solution is not particularly limited, and it does not affect subsequent grinding, spray drying and other steps. Specifically, the second mixed solution can be obtained by dissolving the second iron phosphate, the second lithium source, the second carbon source, and the second M source in a solvent, and the solvent includes but is not limited to deionized water.
[0106] According to a specific embodiment of the present invention, the solid content of the second slurry is 35wt%-50wt%, and the grinding is performed so that the particle size D of the second slurry is 50 The grinding method is not particularly limited and can be selected according to the actual situation in the art, as long as the particle size of the slurry is within the target range, such as by sand grinding.
[0107] According to a specific embodiment of the present invention, the particle size D of the first slurry 50 Smaller than the particle size D of the second slurry 50, and the difference is not less than 0.15μm, thereby obtaining a first slurry with a smaller particle size and a second slurry with a larger particle size. The slurries of different particle sizes are blended, and the slurry particles are in a solution state, so the mixing uniformity is excellent, and the mixed gradation of large and small particles is achieved in the slurry stage. In the subsequent sintering and crystallization process, the particle growth degree grows with the level of the primary particles, which greatly optimizes the particle grading of the material, and the particles are more tightly bonded, so as to prepare a positive electrode active material with both high capacity and high compaction density performance.
[0108] (3) The first slurry and the second slurry are mixed, and the mixture is spray-dried and sintered to obtain the positive electrode active material.
[0109] According to a specific embodiment of the present invention, the mixing ratio of the first slurry and the second slurry is not particularly limited, and those skilled in the art can make reasonable adjustments according to the circumstances. As some specific examples, the first slurry and the second slurry are mixed in a mass ratio of (3:7)-(7:3), such as 3:7, 2:3, 1:1, 3:2, 7:3, etc.
[0110] According to a specific embodiment of the present invention, the inlet air temperature and outlet air temperature of the spray drying are not particularly limited, that is, the slurry can be dried, and preferably the water content of the product after spray drying is ≤3.0%. As some specific examples, the inlet air temperature of the spray drying can be 220°C-280°C, and the outlet air temperature can be 100°C-120°C.
[0111] According to a specific embodiment of the present invention, the sintering temperature and time are not particularly limited, and those skilled in the art can reasonably adjust them according to the situation. As some specific examples, the sintering temperature can be 720°C-830°C, and the sintering time can be 6h-12h. Furthermore, the sintering is preferably carried out in an inert atmosphere, such as nitrogen.
[0112] The third aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0113] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.
[0114] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.
[0115] The positive electrode active material includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.
[0116] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present invention does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.
[0117] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.
[0118] These materials are all commercially available.
[0119] The fourth aspect of the present invention provides a battery, which comprises the positive electrode sheet according to the third aspect of the present invention, so that the battery has an excellent cycle life.
[0120] A battery is a battery that can be used again by recharging the active materials after discharge.
[0121] It is understandable that the battery proposed in the present invention is a lithium-ion battery.
[0122] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0123] [Negative electrode]
[0124] In the battery, the negative electrode plate may be lithium metal or a lithium-containing alloy.
[0125] In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.
[0126] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.
[0127] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0128] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0129] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethylcellulose CMC-Na), and PTC thermistor materials.
[0130] [Electrolyte]
[0131] The electrolyte may include an electrolyte salt and a solvent.
[0132] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0133] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0134] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0135] [Isolation film]
[0136] As the above-mentioned isolation membrane, the present invention has no particular limitation and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs, for example, it can include a combination of at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.
[0137] The fifth aspect of the present invention provides an electric device, which includes the battery described in the fourth aspect. Specifically, the battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can include but is not limited to mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.
[0138] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0139] The relevant parameters in the following examples and comparative examples were obtained by testing using the following methods:
[0140] (1) Morphology test: obtained by scanning electron microscope Regulus 8100 of Hitachi, Japan;
[0141] (2) X-ray diffraction (XRD) test: obtained by SmartLab 9kW X-ray diffractometer of Rigaku Corporation;
[0142] (3) Median particle size D 50 : Measured by Marvern's Mastersizer 3000 laser particle size analyzer;
[0143] (4) Average primary particle size: A scanning electron microscope image of the prepared lithium iron phosphate positive electrode active material was taken at a magnification of 30.0K, and the average primary particle size was calculated using LIBMAS and Nano Measurer software;
[0144] (5) Specific surface area (BET) test: obtained by using Micromeritics' Tristar 3020 surface area analyzer;
[0145] (6) Powder compaction density test: Weigh 1g of the prepared lithium iron phosphate positive electrode active material and put it into a compaction mold. Put the mold into a compaction device to test the result under a pressure of 30KN;
[0146] (7) Particle size distribution test: The prepared lithium iron phosphate positive electrode active material was photographed at 30.0K magnification using a scanning electron microscope, and statistical data was obtained using LIBMAS analysis software;
[0147] (8) Particle size volume distribution test: obtained by testing with Marvern's Mastersizer 3000 laser particle size analyzer;
[0148] (9) Electrochemical performance test: A button half-cell was used for testing, with a test voltage of 2.5V-4.2V. The battery was charged to 4.2V using a constant current and constant voltage charging method, and discharged to 2.5V using a constant current and discharge method. The charge and discharge current was 0.1C for 2 cycles; then 0.2C for 1 cycle; then 0.33C for 1 cycle; then 0.5C for 1 cycle; then 1C for 1 cycle; then 2C for 1 cycle, with the cut-off voltage condition being the same as 0.1C.
[0149] Example 1
[0150]
Preparation of lithium iron phosphate positive electrode active material
[0151] (1) 5004.0 g of Fe / P with a molar ratio of 0.970 and a specific surface area of 10.0 m 2 / g and iron phosphate with a primary particle size of 90nm are mixed with 1235.10g of lithium carbonate, 420g of glucose, 150g of polyethylene glycol, titanium dioxide, ammonium metavanadate, tungsten trioxide, antimony trioxide and 11250g of pure water are added, and mixed in a stirred mill to form a first mixed solution; the first mixed solution is put into a sand mill and sanded at below 45°C, and the sanding particle size D is controlled. 50 The particle size is 0.25 μm and the solid content is 38 wt % to obtain a first slurry;
[0152] (2) 4008.0 g of Fe / P with a molar ratio of 0.960 and a specific surface area of 8.0 m 2 / g and iron phosphate with a primary particle size of 150nm and 984.0g of lithium carbonate are mixed, 305g of glucose, 120g of polyethylene glycol, 8.20g of titanium dioxide and 8830g of pure water are added in a stirred mill to form a second mixed solution; the second mixed solution is put into a sand mill and sanded at below 45°C to control the sanding particle size D 50 The particle size was 0.65 μm and the solid content was 38 wt % to obtain a second slurry;
[0153] (3) The first slurry and the second slurry were stirred evenly in a stirring tank at a mass ratio of 7:3 to obtain a third slurry; the third slurry was spray-dried, and the feed inlet temperature was controlled to be 260° C. and the discharge port temperature was controlled to be 110° C. to obtain a spray material precursor; the spray material precursor powder was calcined at a high temperature under a nitrogen atmosphere, and the sintering temperature was controlled to be 800° C. and the sintering time was controlled to be 12 h; and then the powder was crushed to control the particle size D 50 The particle size of the primary particles is 1.4 μm, and the average primary particle size is 160 nm, thereby obtaining a high-capacity and high-density lithium iron phosphate positive electrode material.
[0154]
Preparation of positive electrode
[0155] The lithium iron phosphate positive electrode active material prepared above, 50% Compressed Denka Black (acetylene black, compression ratio of 50%), and polyvinylidene fluoride (PVDF) are dispersed in N-methylpyrrolidone (NMP) in a mass ratio of 96.5:1.5:2, and after being evenly dispersed by ball milling, they are coated on aluminum foil and vacuum dried to obtain a positive electrode sheet.
[0156]
Preparation of negative electrode sheet
[0157] The negative electrode uses a Li metal sheet.
[0158]
Preparation of electrolyte
[0159] A 1.1 mol / L LiPF6 solution was used as the electrolyte, with an equal volume mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) as the solvent.
[0160]
Isolation film
[0161] Celgard polypropylene film was used as the isolation membrane.
[0162] The positive electrode sheet, the separator, the negative electrode sheet and the electrolyte are assembled into a button-type half-cell.
[0163] The lithium ion batteries containing positive electrode active materials of Examples 2-6 and Comparative Examples 2-3 are the same as those of Example 1 except for some different parameters (see Table 1).
[0164] The scheme of comparative example 1 is specifically as follows:
[0165] (1) 2784.0 g of Fe / P with a molar ratio of 0.970 and a specific surface area of 10.0 m 2 / g and iron phosphate with a primary particle size of 90nm, 1197.0g Fe / P molar ratio of 0.960, specific surface area of 8.0m 2 / g and iron phosphate with a primary particle size of 150nm and 984.30g of lithium carbonate are mixed, 310g of glucose, 120g of polyethylene glycol, 16.80g of titanium dioxide, 13.50g of ammonium metavanadate and 8890g of pure water are added and mixed in a stirred mill to form a first mixed solution; the first mixed solution is put into a sand mill and sanded at below 45°C to control the sanding particle size D 50 The particle size is 0.45 μm and the solid content is 38 wt % to obtain a first slurry;
[0166] The first slurry is spray-dried, and the feed port temperature is controlled to be 245° C. and the discharge port temperature is controlled to be 95° C. to obtain a first precursor having a particle size D50 of 25 μm and a moisture content of ≤3.0%;
[0167] (2) The first precursor powder is calcined at high temperature in a nitrogen atmosphere, the sintering temperature is controlled to be 800°C, and the sintering time is 12 hours; then it is crushed to control the particle size D 50 The particle size of the primary particles is 1.5 μm, and the average primary particle size is 180 nm, thereby obtaining a lithium iron phosphate positive electrode material.
[0168] The primary particle size distribution data of the positive electrode active materials obtained in Examples 1-6 and Comparative Examples 1-3 are shown in Table 2, and the performance parameters of the positive electrode active materials are shown in Table 3.
[0169] The difference between Example 2 and Example 1 is that the mixing ratio of the first slurry and the second slurry is adjusted; the difference between Example 3 and Example 1 is that the D of the first slurry and the second slurry is adjusted. 50 The difference between Example 4 and Example 1 is that the selection of M source is adjusted, Sb is removed, and Ti content is increased; the difference between Example 5 and Example 1 is that the particle size of the first iron phosphate, the D of the first slurry and the second slurry are adjusted. 50 Compared with Example 1, Example 6 is different in that the particle size of the first iron phosphate, the particle size of the second iron phosphate, the D of the first slurry and the second slurry are adjusted. 50 ; At the same time, adjust the addition amounts of titanium dioxide, ammonium metavanadate, tungsten trioxide, and antimony trioxide in step (1) so that the chemical formula is as shown in Table 3.
[0170] Compared with Example 1, Comparative Example 1 is different in that the first slurry and the second slurry are not prepared separately, but the mixed solution containing the first iron phosphate and the mixed solution containing the second iron phosphate are mixed at the same time, and then ground, dried and calcined, and the raw materials do not contain tungsten trioxide and antimony trioxide; Compared with Example 1, Comparative Example 2 is different in that the D of the first slurry is adjusted. 50 and the mixing ratio of the two slurries; Comparative Example 3 is compared with Example 1, the difference is that the D of the second slurry is adjusted 50 .
[0171] Table 1
[0172]
[0173] In Table 1, “ / ” means no addition or none.
[0174] Table 2
[0175]
[0176] In Table 1, “ / ” means none.
[0177] Table 3
[0178]
[0179] Result analysis:
[0180] Compared with Comparative Examples 1-3, the positive electrode active materials prepared by the method provided by the present invention (ie, Examples 1-6) have higher compaction density, better rate performance, and higher capacity.
[0181] in, Figure 1 This is a SEM image of the lithium iron phosphate positive electrode active material prepared in Example 1, from which it can be seen that mixed particles of various different particle sizes are blended. Figure 2 This is the XRD diagram corresponding to the material, and it can be seen that it has a lithium iron phosphate structure. Figure 3 This is the particle size distribution curve of the primary particles of the material. It can be seen that it has two obvious characteristic peaks. Figure 5 The charge and discharge cycle test results of the material are combined Figure 1 and Figure 3 It can be seen that the material prepared in Example 1 is in a multi-stage blending form, so that the material has a higher compaction density and better electrochemical properties.
[0182] Similarly, the remaining examples have the same excellent effects. Compared with Example 1, Example 4 changes the selection of M element and removes Sb. The results show that it does not affect the compaction density of the positive electrode active material, but reduces the capacity of the battery containing the positive electrode active material, but it is still higher than that of Comparative Examples 1-3, indicating that the selection of M source is preferably Sb source.
[0183] Compared with Example 1, the difference between Comparative Example 1 and Example 1 is that two materials with different primary particle sizes are directly mixed, and then ground, dried and calcined. Therefore, the preparation method does not achieve mixed gradation of large and small particles in the slurry stage, and the mixing uniformity is poor. This disadvantage is further magnified in the subsequent calcination process. Figure 4It can be seen that the particle size number distribution curve of the primary particles of the material has only one obvious characteristic peak, which also proves that the material has not achieved multi-stage blending, thus resulting in a decrease in the compaction density of the prepared positive electrode active material and a decrease in the capacity of the battery containing it.
[0184] Comparative Example 2 is compared with Example 1, the difference is that D 50 The mass ratio of the slurry mixture is different. 50 With the second slurry D 50 It is relatively close (the difference is 0.05 μm, which is not within the scope of the present invention), and the proportion of the second slurry is relatively high, and a good grading effect cannot be achieved, so it is impossible to take into account both high capacity and high compaction density performance.
[0185] Similarly, the difference between Comparative Example 3 and Example 1 is that the D 50 Different, the D of the first slurry in this comparative example 50 With the second slurry D 50 The difference is 0.1 μm, which is not within the specified range of the present invention, and a good grading effect cannot be achieved, so both high capacity and high compaction density performance cannot be taken into account.
[0186] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0187] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: The lithium iron phosphate is a secondary particle formed by agglomeration of primary particles, and a particle size distribution curve of the primary particles presents two characteristic peaks; Among them, the highest characteristic peak is the first characteristic peak, and the first characteristic peak is at R A 100nm-250nm, the first characteristic peak is R A The corresponding quantity percentage X A 44%-54%; The second characteristic peak of the primary particles has a peak position R B The second characteristic peak is 270nm-400nm, and the peak position of the second characteristic peak is R B The corresponding quantity percentage X B It is 2.0%-8.0%.
2. The positive electrode active material according to claim 1, characterized in that In the particle size distribution curve of the primary particles, there is a first minimum value R between the first characteristic peak and the second characteristic peak. AO , the first minimum value R AO The corresponding particle size range is 250nm-300nm, and the first minimum value R AO The corresponding quantity percentage X AO 1.0%-5.0%; Optionally, the peak index λ of the positive electrode active material is 5%-20%; Where λ=(X B -X AO ) / X B ×100%; X AO is the first minimum value R between the first characteristic peak and the second characteristic peak AO The corresponding quantity percentage; X B The second characteristic peak position R B The corresponding percentage of quantity.
3. The positive electrode active material according to claim 1 or 2, characterized in that: The D of the primary particles 50 0.1μm-1.0μm; Optionally, the secondary particles have a D 50 0.5μm-1.6μm; Optionally, the compaction density of the positive electrode active material is 2.55 g / cm 3 -2.75g / cm 3 ; Optionally, the specific surface area of the positive electrode active material is 11 m 2 / g-15m 2 / g.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The positive electrode active material includes a substrate and a carbon coating layer coated on the surface of the substrate; Wherein, the matrix has a composition shown in Formula I: Li 1+a Fe b M c (PO4) d Formula I; Among them, -0.1≤a≤0.1, 0≤b≤1, 0≤c≤0.5, 0≤d≤1; M is at least one selected from La, Ce, Cr, Mo, Ca, Hf, Ti, Fe, Zn, Y, Zr, W, Nb, Sm, Sb, Co, Ni, V, Mg, Na, B and Al; Preferably, M is Sb, and at least one of Al, W, Co, V and Ti.
5. A method for preparing a positive electrode active material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: A first mixed solution containing a first iron phosphate, a first lithium source, a first carbon source, and a first M source is prepared, and the first slurry is obtained by grinding; A second mixed solution containing a second iron phosphate, a second lithium source, a second carbon source, and a second M source is prepared, and the second mixed solution is ground to obtain a second slurry; The first slurry and the second slurry are mixed, and the mixture is spray-dried and sintered to obtain the positive electrode active material; Wherein, the particle size of the first iron phosphate is 80nm-200nm; the particle size of the second iron phosphate is 60nm-150nm; The first slurry particle size D 50 Smaller than the particle size D of the second slurry 50 , and the difference is not less than 0.15μm.
6. The preparation method according to claim 5, characterized in that: The specific surface area of the first iron phosphate is 7 m 2 / g-13m 2 / g; Optionally, the specific surface area of the second iron phosphate is 5m 2 / g-12m 2 / g.
7. The preparation method according to claim 5, characterized in that: The D of the first slurry 50 0.15μm-0.50μm; Optionally, the D of the second slurry 50 0.35μm-1.00μm.
8. The preparation method according to claim 5, characterized in that: The inlet air temperature of the spray drying is 220°C-280°C, and the outlet air temperature is 100°C-120°C; Optionally, the first slurry and the second slurry are mixed in a mass ratio of (3:7)-(7:3); Optionally, the sintering temperature is 720° C.-830° C., and the sintering time is 6 h-12 h.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 4 or the positive electrode active material prepared by the preparation method according to any one of claims 5 to 8.
10. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 9.
11. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.
Citation Information
Patent Citations
Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery
CN114068917A
Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery
CN114068919A
Lithium iron phosphate precursor and preparation method thereof, lithium iron phosphate material and lithium ion battery
CN117023543A
Lithium manganese iron phosphate composite material as well as preparation method and application thereof
CN117855432A
Lithium iron phosphate positive electrode material and preparation method thereof, positive plate and lithium battery
CN118145616A